2012
DOI: 10.1098/rsta.2011.0194
|View full text |Cite
|
Sign up to set email alerts
|

Distributed inference in wireless sensor networks

Abstract: Statistical inference is a mature research area, but distributed inference problems that arise in the context of modern wireless sensor networks (WSNs) have new and unique features that have revitalized research in this area in recent years. The goal of this paper is to introduce the readers to these novel features and to summarize recent research developments in this area. In particular, results on distributed detection, parameter estimation and tracking in WSNs will be discussed, with a special emphasis on s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
66
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 110 publications
(66 citation statements)
references
References 126 publications
(165 reference statements)
0
66
0
Order By: Relevance
“…Our results for QAM can be viewed as a generalization of classical results on the hard decision penalty for binary communication in [1]- [3], while our results for larger PSK alphabets draw on the relatively recent low-SNR analysis in [4]. Prior work: There is a large body of related literature dating back more than three decades on the broad subjects of "multiterminal inference" [5]- [7], "distributed hypothesis testing" [8]- [10], and "distributed detection" [11]- [15]. In general, the setting in these problems is to have multiple agents forward quantized observations to a fusion center which then applies a detection or estimation rule according to a certain performance objective.…”
mentioning
confidence: 99%
“…Our results for QAM can be viewed as a generalization of classical results on the hard decision penalty for binary communication in [1]- [3], while our results for larger PSK alphabets draw on the relatively recent low-SNR analysis in [4]. Prior work: There is a large body of related literature dating back more than three decades on the broad subjects of "multiterminal inference" [5]- [7], "distributed hypothesis testing" [8]- [10], and "distributed detection" [11]- [15]. In general, the setting in these problems is to have multiple agents forward quantized observations to a fusion center which then applies a detection or estimation rule according to a certain performance objective.…”
mentioning
confidence: 99%
“…Since many practical channel models such as path-loss model and Rayleigh fading model have non-negative channel gains, we assume that b is a non-negative vector in the rest of this section. 1 Since this is a likelihood ratio test, all the other rules are dominated. Therefore, their removal does not result any loss in network performance.…”
Section: Lemmamentioning
confidence: 99%
“…Jamming attacks in detection networks have a significant impact on today's world due to the wide range of applications of these networks [1]. Therefore, several attempts have been made in the past literature to address jamming attacks in detection networks.…”
Section: Introduction and System Modelmentioning
confidence: 99%
“…Thus, to prove thatŴ is a primitive matrix, it is sufficient 3 to show thatŴ has a single eigenvalue with maximum modulus of 1. In [27], the authors showed that when…”
Section: ) All Eigenvalues Ofŵ Are In a Unit Circle;mentioning
confidence: 99%
“…Distributed detection is a well studied topic in the detection theory literature [1]- [3]. The traditional distributed detection framework comprises of a group of spatially distributed nodes which acquire the observations regarding the phenomenon of interest and send them to the fusion center (FC) where a global decision is made.…”
Section: Introductionmentioning
confidence: 99%